Comparative Performance of MM Instant and Conventional Mortars in Residential Plastering - Annisa Nur Rakhmawati; Khalilah Daud Isaac Makhmut; Aria Dian Tri Wahyuni (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Plastering is a critical finishing activity that influences construction duration, cost efficiency, and the final quality of residential buildings. Although conventional mortar mixed on-site remains widely used, MM instant mortar is increasingly adopted because of its more controlled composition and simplified application process. This study aims to compare the performance of MM instant mortar and conventional mortar in terms of labor productivity, implementation cost, and plastering quality. A quantitative comparative method was applied to residential building plastering work, with an observed area of 484 m² for each mortar type. Productivity was assessed based on the completed plastering area per workday, while costs were calculated from materials, labor, equipment, waste, and potential rework. Plastering quality was evaluated using compressive strength, bond strength, surface flatness, and defect level. The findings show that MM instant mortar achieved an average productivity of 14.19 m²/day, compared with 9.92 m²/day for conventional mortar, representing a 43.04% increase. The direct cost of MM instant mortar was Rp59,100/m², which was 10.67% higher than the Rp53,400/m² required for conventional mortar. However, after accounting for rework costs arising from defects, the effective cost of MM instant mortar was Rp60,341/m², slightly lower than the Rp60,876/m² recorded for conventional mortar. MM instant mortar also demonstrated superior performance in compressive strength, bond strength, surface flatness, and material waste. These findings indicate that MM instant mortar provides advantages in productivity, effective cost efficiency, and quality consistency, particularly for projects prioritizing faster completion and improved workmanship. Conversely, conventional mortar remains competitive when minimizing initial material cost is the primary consideration. This study contributes practical evidence for selecting plastering materials based on trade-offs among productivity, cost, and construction quality in residential building projects.